Post-Pandemic Covid-19 Food Security Strategy Model in Coastal Community and Fisherman Households in Lampung Province - Helvi Yanfika; Puspita Yuliandari; Herman Yulianto; Irwan Effendi; Indah Nurmayasari; Dewangga Nikmatulloh (Open Global Scientific Journal, 2023)
ishermen are one part of the community members who have the lowest level of welfare. The COVID-19 pandemic is an event that causes the spread of the coronavirus disease 2019 around the world. The pandemic has caused global socio-economic disruption, the postponement or cancellation of sporting and cultural events, and widespread concern about stock shortages driving panic buying. A household is said to have food security if its inhabitants are not in a state of hunger or feel threatened by hunger. The linkages between the lives of coastal communities and fishermen in Lampung Province are quite concerning, coupled with the COVID-19 pandemic requiring special treatment to improve their welfare and standard of living, one of which is by increasing food security for coastal communities and fishermen. The most appropriate effort is to carry out a post-COVID-19 Pandemic Food Security Strategy modeling for Coastal Community and Fisherman Households in Lampung Province. The research was carried out from April to September 2022 in Labuhan Maringai subdistrict, East Lampung Regency. Sampling was done purposively. The data collected from the survey results have been analyzed statistically descriptive and inferential. The level of food security for the respondent's family is in the moderate category, meaning that the respondent can provide, reach and use it quite well but not optimally. The community has not been able to ensure that the food security component can run consistently at any time. This happens because the income of fishing households is very unpredictable, this can also determine the ability of the family to provide food. The influence of the education level of a housewife has an indirect effect through her nutritional knowledge. Food knowledge has a more direct influence on food security, meaning that the knowledge of housewives related to food is the basis for action in realizing food security at the family level.